Analysis of Compliance Level of Nurse Personal Protection Use in Royal Prima General Hospital - Sri Lestari Ramadhani Nasution; Nadratul Ulya; Sinta Ayu Setiawan; Sri Wahyuni Nasution (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
This study aimed to determine the level of compliance with the use of personal protective equipment as prevention of work accidents. This research was conducted using quantitative methods with a cross-sectional approach in the Emergency Unit and Intensive Care Unit at the Royal Prima General Hospital.   The results showed a relationship between age and adherence to the use of PPE with p = 0.002. There is no correlation between years of service and compliance with the use of PPE with p-value = 0.75. There is a relationship between knowledge of compliance with the use of PPE with p-value = 0.009. There is a relationship between attitudes towards compliance with the use of PPE with p = 0.002. There is a relationship between the availability of facilities and compliance with the use of PPE with a p-value of 0.000. There is a relationship between compliance training on the use of PPE with p-value = 0.004. There is a control relationship to compliance with the use of PPE with p-value = 0.002.